Getting in the Scrap: the Salvage Drives of World War II - Hugh Rockoff (Rutgers University, Department of Economics, 2000)
During World War II Americans were asked to salvage a long list of materials for the war effort including paper, tin, iron and steel, rubber, and even silk stockings and cooking fat. Stories about the salvage drives have become a staple in both popular and scholarly histories of the home front, and in film documentaries, because the drives appear to illustrate the potential importance of non-economic motives such as patriotism and community spirit. Here I reexamine the major drives, especially the iron and steel and rubber drives. Despite the propaganda that accompanied them, the drives were able to increase scrap collections only by relatively small margins above what would have been collected during prosperous peacetime periods. The impact of the familiar calculus of profit and loss, and the impact of the maneuvering of special interests for advantage, moreover, can be seen at every turn. It turns out that the scrap drives, and the propaganda and patriotism that accompanied them, had a far more limited impact on the economy than might be imagined from the enthusiastic portrayal of them in the historical literature. While the impact of the drives on the economy was limited, the impact of the drives on civilian morale, may well have been substantial.
Keywords: N4; 330